Construction of intelligent water saving irrigation control system based on water balance. Issue 17 (2018) - Zhang, S.; Wang, M.; Shi, W.; Zheng, W.
Abstract: water saving irrigation is an important way to solve the shortage of water resources in arid areas. The design of water saving irrigation system based on water balance theory can effectively solve the problem of uneven distribution of soil moisture and system decision lag. This paper introduces the theoretical realization of water balance method, and then introduces the calculation method of water supplement and crop transpiration. On the basis of the theoretical research, this paper introduces the intelligent water saving irrigation control system designed by the method of the Agricultural Internet of things, and gives the detailed design method of the system hardware and software of. The system is applied in Xiaotangshan, Beijing. The application results show that intelligent water saving irrigation based on water balance can effectively implement irrigation.